Advances in relapsed/refractory follicular lymphoma therapeutics. Issue 1 (19th October 2019) - Kharchenko, Evgeniya V.; Sweetenham, John W.
Abstract: Of 75 000 new cases of Non‐Hodgkin lymphoma (NHL) expected in 2018 in USA, World Health Organization (WHO) data suggest that follicular lymphoma (FL) and diffuse large B‐cell lymphoma (DLBCL) will be the two most common types. On average, each year, 15 000 new cases of FL are diagnosed in the United States alone. Despite dramatic improvements worldwide in the treatment of FL, such as the emergence of anti‐CD20 agents, FL cannot be cured yet. There is no widely agreed standard of care for the first line therapy of FL. Current options include "watch and wait" strategies, rituximab monotherapy, multi‐drug therapy of rituximab and bendamustine or CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone), CVP (cyclophosphamide, vincristine, prednisones), or combinations with the new anti‐CD 20 monoclonal antibody obinutuzumab. Even with average of 80% response rate to initial therapy 20% of patients relapse within 2 years and there is no clear consensus on further management. However, a diverse set of new drugs with different mechanisms of action are available in a relapse setting. These drugs have extended overall survival (OS) up to 12 years. An indolent course of FL is manifested by varying periods of remissions and relapses that can potentially progress to transformation into either other hematologic malignancy (eg, DLBCL) or become chemo‐refractory. Considering the chronic nature of FL, physicians should strive for both efficacy of treatment and possible extended‐length remissions, and for good patient quality of life and limited toxicity.